Development and Testing of the Dysmenorrhea Symptom Interference (DSI) Scale. (April 2021) - Chen, Chen X.; Murphy, Tabitha; Ofner, Susan; Yahng, Lilian; Krombach, Peter; LaPradd, Michelle; Bakoyannis, Giorgos; Carpenter, Janet S.
Dysmenorrhea affects most reproductive-age women and increases the risk of future pain. To evaluate dysmenorrhea interventions, validated outcome measures are needed. In this two-phase study, we developed and tested the dysmenorrhea symptom interference scale. During the scale-development phase ( n = 30), we created a nine-item scale based on qualitative data from cognitive interviews. During the scale-testing phase ( n = 686), we evaluated reliability, validity, and responsiveness to change. The scale measures how dysmenorrhea symptoms interfere with physical, mental, and social activities. Internal consistency was strong with Cronbach's α > 0.9. Test–retest reliability was acceptable ( r = 0.8). The scale showed satisfactory content validity, construct validity (supported by confirmatory factor analysis), concurrent validity, and responsiveness to change. The minimally important difference was 0.3 points on a scale with a possible total score ranging from 1 to 5. This new psychometrically sound scale can be used in research and clinical practice to facilitate the measurement and management of dysmenorrhea.